PENGUATAN PENDIDIKAN KARAKTER SISWA MELALUI LAGU DAERAH BUGIS ”ININNAWA SABBARAE” - Kasma F. Amin; Muliadi Muliadi; Ainul Alim Rahman (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
This activity aims to strengthen character education by instilling the values of patience, kindness, and simplicity in students through the Bugis Ininnawa Sabbarae folk song. The strengthening of character education through bugis folk songs is thought to be relevant to the phenomenon of hyper reality life. Ininnawa sabbarae is a Bugis folk song as a local cultural heritage that is usually sung by parents for the cultivation of character in their children. The implementation method is training and introduction of Bugis folk songs through the stages of planning, implementing, observing, and evaluating. The target of this training activity is teachers and students with 20 students involved. The results of the activity showed about the presentation of the increase in students' knowledge about the characters contained in the Bugis Ininnaawa Sabbarae folk song.  There was also a 60% increase in the ability of students to understand the character of patience, good character and simple character.  Students experienced a 100% increase in interest in knowing their folk songs after understanding the character content in the song Ininnawa Sabbarae. Based on the answers from the results of the return after conducting training on the introduction of song character content in the Bugis area with the singing method, there was an increase in character understanding, and students felt very satisfied